1966
DOI: 10.1161/01.res.19.2.317
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Norepinephrine Stores and the Contractile State of Heart Muscle

Abstract: In order to assess the role played by endogenous norepinephrine (NE) stores in the intrinsic contractile state of cardiac muscle, the right ventricular papillary muscles from normal cats and cats with cardiac NE depletion produced by chronic cardiac denervation or reserpine pretreatment were studied. The contractile state of NE-depleted ventricular myocardium was found to be normal. The resting and active length-tension curves, the forcevelocity relations, and the augmentation of isometric tension achieved by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1967
1967
1998
1998

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…3,4 The 24-h cycle of HRV (which is defined as a circadian rhythm) may be an important factor because high sympathetic activity that persists throughout a 24-h period may acceleratereceptor down-regulation 19 and promote a reduction of catecholamine stores in the heart. 20,21 Thus, the patients with reduced circadian rhythmicity of HRV may have impaired autonomic nervous function such as diabetic neuropathy, 12 prior myocardial infarction 13,14 or congestive heart failure. 15,16 Previous studies demonstrated that patients with NSVT also have reduced circadian variation of HRV; 7,10 however, we noted that some patients with NSVT have a preserved circadian rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The 24-h cycle of HRV (which is defined as a circadian rhythm) may be an important factor because high sympathetic activity that persists throughout a 24-h period may acceleratereceptor down-regulation 19 and promote a reduction of catecholamine stores in the heart. 20,21 Thus, the patients with reduced circadian rhythmicity of HRV may have impaired autonomic nervous function such as diabetic neuropathy, 12 prior myocardial infarction 13,14 or congestive heart failure. 15,16 Previous studies demonstrated that patients with NSVT also have reduced circadian variation of HRV; 7,10 however, we noted that some patients with NSVT have a preserved circadian rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the aim of the present investigation was to determine the effects of hyper-and hypothyroidism on: (a) the intrinsic contractile properties of the myocardium in the presence and absence of intact norepinephrine stores; (b) the contractile responses of the myocardium to various inotropic stimuli; and (c) the high energy phosphate stores in the myocardium. The recent development of methods for detailed and quantitative analysis of mechanical characteristics of isolated cat papillary muscle (8), removed from the nervous, humoral, and metabolic influences that exist in vivo, and the ability to compare the function of muscles obtained from different groups of animals (9), permit critical examination of these problems. In addition, although interpretation of many previous studies of myocardial high energy phosphate stores in altered thyroid states (10)(11)(12)(13)(14) was limited by the extreme lability of these energy stores, recent modifications of biopsy and analytic techniques have made possible the accurate assessment of these stores in vivo (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies using isolated heart muscle have demonstrated no significant differences in the resting contractile state of the myocardium between normal and norepinephrine depleted specimens (Cairoli et al 1962;Spann et al 1966). Spann et al suggested that norepinephrine deple tion itself would not change the intrinsic contractile state of the myocardium (Spann et al 1966).…”
Section: Discussionmentioning
confidence: 99%
“…Spann et al suggested that norepinephrine deple tion itself would not change the intrinsic contractile state of the myocardium (Spann et al 1966). However, another report describes a positive relationship between myocardial norepinephrine depletion and defective myocardial contractility ).…”
Section: Discussionmentioning
confidence: 99%